2022
DOI: 10.3390/cells11203243
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Novel Biological Properties of Diterpenes Isolated from Plectranthus ornatus Codd. In Vitro and In Silico

Abstract: Plectranthus ornatus Codd, the genus Plectranthus of the Lamiaceae family, has been used as traditional medicine in Africa, India and Australia. Pharmacological studies show the use of this plant to treat digestive problems. In turn, leaves were used for their antibiotic properties in some regions of Brazil to treat skin infections. The present study examines the anti-inflammatory, antioxidant and cytotoxic effects of the halimane and labdane diterpenes (11R*,13E)-11-acetoxyhalima-5,13-dien-15-oic acid (HAL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Roy demonstrated strong antiproliferative and cytotoxic effects against tumor cells, with low IC50 values in various cell lines. Additionally, a new fluorescence derivative, BODIPY-Roy, confirmed the increased intracellular fluorescence associated with Roy's antiproliferative activity, suggesting its potential as a basis for the development of new therapeutic strategies against glioblastoma [1,2].…”
Section: Plectranthus: From Traditional Medicine To Brain Tumor Thera...mentioning
confidence: 79%
See 1 more Smart Citation
“…Roy demonstrated strong antiproliferative and cytotoxic effects against tumor cells, with low IC50 values in various cell lines. Additionally, a new fluorescence derivative, BODIPY-Roy, confirmed the increased intracellular fluorescence associated with Roy's antiproliferative activity, suggesting its potential as a basis for the development of new therapeutic strategies against glioblastoma [1,2].…”
Section: Plectranthus: From Traditional Medicine To Brain Tumor Thera...mentioning
confidence: 79%
“…The compound displayed cytotoxic activity against glioblastoma, inducing apoptosis through the intrinsic mitochondrial pathway and disrupting the G2/M cell cycle. Its antitumor efficacy surpassed that of the first-line treatment temozolomide in glioblastoma and showed potential against triple-negative breast cancer, reducing cell viability, inducing İD apoptosis, and inhibiting cell migration and invasion, indicating potential antimetastatic effects [1].…”
Section: Plectranthus: From Traditional Medicine To Brain Tumor Thera...mentioning
confidence: 99%
“…Pharmacological studies of P. ornatus have shown its antibiotic, anti-in ammatory, antioxidant, and cytotoxic effects on leukemia and lung cancer cells (Sitarek et al, 2022). The P. ornatus extract has also shown antioxidant capacity, mainly associated with compounds such as rosmarinic, caffeic, and o-hydroxycinnamic acids (Medrado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the anticancer activity of a natural compound, in this case, daphnoretin, was tested by Huang et al [ 9 ] in human chronic myeloid leukemia cells. As their main finding, the authors observed that daphnoretin intervened at the level of the cell cycle, inhibiting tumor growth and also inducing megakaryocytic differentiation.…”
mentioning
confidence: 99%